2017
DOI: 10.18517/ijaseit.7.2.2035
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Wastewater Containing Hexavalent Chromium Using Zeolite Ceramic Adsorbent in Adsorption Column

Abstract: Natural Zeolites in powdered form have commonly used as adsorbent and one of the most crucial compound in water treatment plant, in filter system of petrochemicals or other processes under environmentally, physically and chemically conditions. But in the form of powder, zeolites are easily washed out in liquid or gas stream. Therefore, a modification would be necessary to solve this problem. Zeolites and clay were modified into ceramic adsorbent to adsorb heavy metal pollutant that is hexavalent chromium Cr (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It has been shown that a longer contact time enhances the adsorption process. The alkaline groups on the surface of the activated carbon bind the cations from the wastewater to the adsorbent surface during the adsorption process in an aqueous solution [18,19].Fe and Al cations must have interacted with the adsorbent during the adsorption process. In this case, the surface layer of the activated carbon is basic.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that a longer contact time enhances the adsorption process. The alkaline groups on the surface of the activated carbon bind the cations from the wastewater to the adsorbent surface during the adsorption process in an aqueous solution [18,19].Fe and Al cations must have interacted with the adsorbent during the adsorption process. In this case, the surface layer of the activated carbon is basic.…”
Section: Resultsmentioning
confidence: 99%
“…where q e is the adsorption capacity (mg g -1 ), C o and C t are the initial and equilibrium concentration of metallic ions in the samples solution (mg L -1 ). V is the volume of testing solution (L) and W is the weight of adsorbent (g) [32], [33].…”
Section: B Methodsmentioning
confidence: 99%
“…Several studies have been conducted on the application of filters in the removal of dyes such as methyl orange (MO) and toxic metals including chromium (Cr). [24][25][26][27][28][29][30] A comparative analysis of the capabilities of the filters used in the above-mentioned studies and the filters fabricated and used in the current study is discussed. The fabricated ceramic filters are deemed to be cost-effective and environmentally friendly because they were derived from natural clay (a sustainable and natural material) and the macadamia nutshells (an agricultural waste product from the macadamia nuts processing industry).…”
Section: Introductionmentioning
confidence: 99%